Utilizing Zakah Fund for Developing Microtakaful Scheme Towards Enhancing Financial Well-Being of Working Asnaf in Kedah - Kadir @ Shahar, Hanita; Azhari, Adilah; Aziz, Nazliatul Aniza; Ridzuan, Muhammad Nasrul (UUM, 2022)
This study aims to develop a Microtakaful scheme utilising the Zkah fund by adopting both quantitative and qualitative methods to identify the factors that influence financial well-being among Asnaf in Kedah. A total of 83 working Asnaf from Skim Bantuan Jayadiri under Lembaga Zakat Negeri Kedah participated in the survey and two representatives from top management of Lembaga Zakat Negeri Kedah were interviewed. A stratified sampling technique was employed and survey data were analysed using partial least squares structural equation modeling (PLS-SEM). The study found that common risks and vulnerabilities faced by the working Asnaf are illnesses that required outpatient treatment, loss of livestock and permanent and temporary disability. The study concluded that in terms of risk coping mechanism, the risks could be covered in the Microtakaful scheme due to the respondents are least likely to seek financial assistance from the government when disaster strikes. The survey result indicates that Protection Needs, Risk coping mechanism and Zakat have significant positive relationship towards financial well-being. The findings highlight that a proposed Microtakaful plan can be applied to the Lembaga Zakat Kedah and other Zakat agency in other states in Malaysia.